2008
DOI: 10.1104/pp.108.119040
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Recycling and Remobilization Are Differentially Controlled by Leaf Senescence and Development Stage in Arabidopsis under Low Nitrogen Nutrition

Abstract: Five recombinant inbred lines (RILs) of Arabidopsis (Arabidopsis thaliana), previously selected from the Bay-0 3 Shahdara RIL population on the basis of differential leaf senescence phenotypes (from early senescing to late senescing) when cultivated under nitrogen (N)-limiting conditions, were analyzed to monitor metabolic markers related to N assimilation and N remobilization pathways. In each RIL, a decrease of total N, free amino acid, and soluble protein contents with leaf aging was observed. In parallel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
210
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(238 citation statements)
references
References 37 publications
21
210
0
2
Order By: Relevance
“…1b). This result corresponded well to those of previous reports (Masclaux et al 2000;Diaz et al 2008). We used this alteration in amino acid profiling in a model experiment to elucidate the regulatory mechanisms of leaf amino acid metabolism.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…1b). This result corresponded well to those of previous reports (Masclaux et al 2000;Diaz et al 2008). We used this alteration in amino acid profiling in a model experiment to elucidate the regulatory mechanisms of leaf amino acid metabolism.…”
Section: Resultssupporting
confidence: 75%
“…1b) indicated that nitrogen compounds were remobilized to the sink tissues during the reproductive developmental stage. This change in amino acid profiling has been reported previously (Masclaux et al 2000;Diaz et al 2008). Conversely, other reports have shown an increase in leaf asparagine content during senescence (Lin and Wu 2004;Lea et al 2007).…”
Section: Discussionmentioning
confidence: 48%
“…It has been shown that elevated autumn temperatures in cold regions can stimulate photosynthetic rates despite the natural shift in photoperiod that marks the beginning of the senescence period (Méthy et al, 1997). This affects the degradation of chlorophyll (Davison, 1991;Fracheboud et al, 2009), and therefore the onset of plant senescence through N and C dynamics (Diaz et al, 2008;Kröger et al, 2007). However, the potential effects of warming on this mechanism of senescence and its consequences for C uptake and allocation have received little attention in climate warming studies.…”
Section: Introductionmentioning
confidence: 99%
“…photosynthetic pigment level, protein content and CO 2 fixation rate) in primary leaves of sunflower plants grown for 42 days. The start of senescence in sunflower plants was associated with a considerable decrease in protein content and specific leaf masses referred as weight (Table 1 These changes may reflect alterations in N and C compound distributions as a consequence of N remobilization, the efficiency of which is related to the ratio between biomass in the sink and source organs (Wiedemuth et al, 2005;Diaz et al, 2008). Since chloroplasts contain the largest amounts of protein in leaves, their breakdown releases most of the nitrogen that is reused by other plant organs.…”
Section: Growth-related Parameters and Photosynthetic Activity Duringmentioning
confidence: 99%